FAIRY COSTUME DESIGN FOR THE THEATER WITH A SUSTAINABILITY CONCEPT APPROACH - Ariana Sadaqah, Zaafira
The concept of sustainability is becoming increasingly important in various industries. In the concept of sustainability there are also principles in textile design such as designs for longevity, designs for low-impact production, and designs for local and ethical production. The application of the concept of sustainability has also begun to be seen, such as the concept of recycling, the use of waste materials, and effective and efficient manufacturing. One of the creative industries that has begun to apply the concept of sustainability is theater. This concept of sustainability encourages the theater industry to innovate more and examine conventional practices in achieving innovation that does not only focus on environmental issues, but also pushes the intellectual level and limits of human creativity. In theatre, costumes play a role in helping to transport the audience to the world and situation of the performance, creating an emotional and intellectual connection with the characters and the audience. Fairies are mythical creatures from folklore and romance that usually have magical powers and live on earth near humans. They are widely used in plays or theatre, from Shakespeare's classic play "A Midsummer Night's Dream" to theatrical children's tales such as Tinkerbell and Maleficent. The purpose of this research is to produce the application of the concept of sustainability to theatrical costumes, especially in fairy costumes by using materials that are in accordance with the concept of sustainability such as low-impact, one of which is textile upcycling material and a longevity system where the resulting output can last a long time, is effective, and efficient. In accordance with the objectives to be achieved, the research methodology and approach uses a combined method, namely qualitative and quantitative methods. Qualitative research is focused on designing, experimenting, exploring, and the result of fairy costumes for theater with a sustainability concept approach. While quantitative as a complement to research in the utilization of textile upcycling material itself with the existence of quantity data regarding the availability of materials obtained to determine the final amount of material used.